Socialization of the Use of the Live Tiktok Shop Feature as a Marketing Method in Increasing Housewives' Home Businesses - Prilosadoso, Basnendar Herry; Nazriah, Ainun; Putra , Johni Eka; Desembrianita , Eva; Mardiah, Ainil (Universitas Pahlawan Tuanku Tambusai, 2024)
The increasingly sophisticated technological progress in this modern era is one of the innovations resulting from the rapid development of technology, namely online sales or digital business. Purwosari Village is one of the villages in Laweyan subdistrict, Surakarta City, Central Java Province, where many residents are involved in managing industrial houses. According to Purwosari sub-district officials, the number of home industries in the village is already large, but home industry players still carry out traditional marketing such as Word of Mouth (WoM) and promotions using the WhatsApp application only. So far, Home Industry players still find it difficult to use digital marketing media so not many people use it. Based on these problems, digital marketing outreach and training was carried out, especially using the Live TikTok Shop feature. The choice of marketing media using TikTok is because this platform is widely used by the general public and has a TikTok Shop which is a social commerce feature with the aim of enabling MSMEs who use this application to promote and sell products. The aim of carrying out this Community Service activity is to optimize marketing activities for home industry digitally so that home industry products in the Purwosari Subdistrict, Laweyan District can cover a wider coverage not only in the surrounding area but can cover all of Indonesia. Community Service Activities in Purwosari Village are carried out by holding outreach and training for all Home Industry players. Based on the activities that have been carried out, Home Industry players who do not yet have a TikTok Shop account can help manage the products produced on the platform and understand how to market them. The result of this socialization and training is an increase in the ability of Home Industry players to utilize the Live TikTik Shop feature and also increase sales of goods produced by the Home Industry.